2021
DOI: 10.1007/s10854-021-05336-4
|View full text |Cite
|
Sign up to set email alerts
|

Novel low Ag-content Sn–Ag–Cu–Sb–Al solder alloys with enhanced elastic compliance and plastic energy dissipation ability by applying rotating magnetic field

Abstract: The main scope of this research is to investigate the impact of rotating magnetic field (RMF) on the physical properties of the Sn-0.5Ag-0.5Cu-2.0Sb-0.1Al (SAC0505SbAl) solder alloy. The application of RMF during molten alloy cooling showed prominent effect on the morphology, thermal properties, and the consequent mechanical characteristics. It was shown that the dendritic morphology was changed from columnar dendrites to equiaxed grains with the application of RMF. In addition, RMF processing modified the eut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Onset The pasty range of SZ, SZN901, SZN902, SZN903, and SZ-ZrO 2 is 10.4, 11.2, 8.2, 7.1, and 12.3 °C respectively. The addition of 0.1 wt.% of Ni expands slightly the temperature interval of the pasty range, which is close to 11.5 °C for Sn-37Pb solders [45] but increasing the ratios of Ni addition decreases the pasty range more than the eutectic Sn-9Zn, as shown in table 2 which allowed better microstructure formation of the Ni added into solder alloys. The ternary alloys have a narrow pasty range with good solidus temperature, particularly the SZN903 solder alloy due to the solder is achieve the composition near to the eutectic point and can be candidate for electronic solder application.…”
Section: Thermal Analysismentioning
confidence: 54%
“…Onset The pasty range of SZ, SZN901, SZN902, SZN903, and SZ-ZrO 2 is 10.4, 11.2, 8.2, 7.1, and 12.3 °C respectively. The addition of 0.1 wt.% of Ni expands slightly the temperature interval of the pasty range, which is close to 11.5 °C for Sn-37Pb solders [45] but increasing the ratios of Ni addition decreases the pasty range more than the eutectic Sn-9Zn, as shown in table 2 which allowed better microstructure formation of the Ni added into solder alloys. The ternary alloys have a narrow pasty range with good solidus temperature, particularly the SZN903 solder alloy due to the solder is achieve the composition near to the eutectic point and can be candidate for electronic solder application.…”
Section: Thermal Analysismentioning
confidence: 54%
“…These indicated that the incorporation of Sb can evidently improve the mechanical properties of SAC105 alloy. The microstructure characteristics of solder alloys inevitably control their mechanical properties (El-Taher et al , 2021; Hammad and Ragab, 2019). The heterogeneous nucleation points increased with the Sb doping, which resulted in the diminution of grain size and the generation of more grain boundaries to hinder dislocation movement (Sun et al , 2016; Bakshi and Agarwal, 2011; Sharma et al , 2015; Billah and Chen, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…When the alloy was stressed, the smaller grains of the alloy could improve the energy consumption of dislocation operation, but when the relative movement between grains occurred, the smaller grains meant more grain boundaries. Sb accumulated at the grain boundaries under the action of Lorentz magnetic force, leading to more obvious lubrication at grain boundaries and promoting the relative sliding of grains (El-Taher et al , 2021; Bai et al , 2021). Therefore, the tensile strength of the Sn-3.5Ag-0.5Sb alloy decreased under the magnetic field.…”
Section: Resultsmentioning
confidence: 99%
“…A new method is to use a rotating magnetic field (RMF) during the solidification of solder alloys (Ripley et al , 2015). The RMF influences the flow and coagulation of molten metals, which eliminates defects, reduces grain size and ultimately improves the overall performance of solder joints (El-Taher et al , 2021; Hammad and Ragab, 2019; Ibrahiem and El-Daly, 2019). Hammad (Hammad and Ragab, 2020) investigated the influence of the RMF on the fine texture and mechanical performance of SACZ (Sn-2.0Ag-0.5Cu-2.0Zn) and found that the grain size of β -Sn and intermetallic compounds (IMCs) decreased and the mechanical performance was enhanced under the RMF.…”
Section: Introductionmentioning
confidence: 99%